The inclusion of children with disabilities in the school context through the supplementary and alternative communication resources (Research, Society and Development, 2020)
The present study aimed to analyze, reflect and discuss the importance of knowing a little more about the inclusion of children with disabilities in the school context from the resources of supplementary and alternative communication and how it can contribute to the development of students who do not have functional speech. It is the 21st century, but we still lack the information and knowledge about how to work in school with these resources in the classroom. For the methodology, we decided to conduct a theoretical and methodological discussion from parts of two features adapted in alternative communication addressed by the authors Manzini and Deliberato. Such resources were found on the technical support portal to assist alternative communication through equipment and special educational material in education, training and recreation for people with physical disabilities, in addition to having chosen the author Mantoan for understanding that she brings a wider concept about Inclusive Education and its contribution to school spaces among other theorists in regards to this subject.